2019
DOI: 10.3390/s19245465
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Electronics Assess the Effectiveness of Transcranial Direct Current Stimulation on Balance and Gait in Parkinson’s Disease Patients

Abstract: Currently, clinical evaluation represents the primary outcome measure in Parkinson’s disease (PD). However, clinical evaluation may underscore some subtle motor impairments, hidden from the visual inspection of examiners. Technology-based objective measures are more frequently utilized to assess motor performance and objectively measure motor dysfunction. Gait and balance impairments, frequent complications in later disease stages, are poorly responsive to classic dopamine-replacement therapy. Although recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…After eliminating 37 duplicates, 99 articles were excluded after screening by titles and abstracts. Two studies did not report sham stimulation results and were removed after reading the full text [ 40 , 41 ]. Although our search space included not only PD but also Parkinsonian syndromes, all studies identified with a randomized design were conducted in PD.…”
Section: Resultsmentioning
confidence: 99%
“…After eliminating 37 duplicates, 99 articles were excluded after screening by titles and abstracts. Two studies did not report sham stimulation results and were removed after reading the full text [ 40 , 41 ]. Although our search space included not only PD but also Parkinsonian syndromes, all studies identified with a randomized design were conducted in PD.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, over the past several years numerous studies have taken advantage of an IMU-based approach to assessing postural stability in healthy as well as patient subjects (e.g., Refs. [35][36][37][38][39][40][41][42][43][44][45][46][47]). The application of computational methods to IMU-based data sets has demonstrated that this method can provide a clinician with a comparable ability to differentiate between individuals with vestibular loss and healthy controls as force platform posturography [48].…”
Section: Imu Measures Of Postural Stability and Implications For Vest...mentioning
confidence: 99%
“…After reviewing titles and abstracts, 51 studies were included, and five additional studies (Forogh et al, 2018;Geroin et al, 2011;Madhavan et al, 2020;Manenti et al, 2016;Tahtis et al, 2014) were included from other systematic reviews on similar topics. After full text review, 19 studies were excluded due to the following reasons: without sham/CG (n = 9) (Alexoudi et al, 2018;Dumont et al, 2015;Hadoush et al, 2018;Mohammadi et al, 2021;Naro et al, 2020;Pilloni et al, 2019;Rezaee et al, 2020;Ricci et al, 2019;Solanki et al, 2021), another population (n = 3) (Jafarzadeh et al, 2019;Maldonado and Bernard, 2021;Manor et al, 2018), another intervention (n = 1) (Koganemaru et al, 2019), and another outcome (n = 6). Finally, 37 articles were included for the systematic reviews and 33 for the meta-analysis (two studies were J o u r n a l P r e -p r o o f 10 excluded from the meta-analysis because of the design (case reports) and two due to incomplete data) (Costa et al, 2020;Forogh et al, 2018;Kaski et al, 2014a;Verheyden et al, 2013).…”
Section: Study Selectionmentioning
confidence: 99%